A Multivariate Analysis of REIT Characteristics on Risk-Adjusted Return - Adams, Peter (2017)
This paper analyzes the relationship of individual financial characteristics on overall real estate investment trust (REIT) performance. Although the functionality of REITs can be quite complex, this study and its results aim to identify which factors have significant influence on returns. Risk-adjusted return, represented by an individual security’s annualized Sharpe Ratio was regressed against several independent financial factors using multiple econometric regression models including ordinary least squares, fixed effects and general method of moments. The results from these three models add confidence to the beta coefficients associated with each individual factor and help shape a broader and more complete analysis of causality. Additionally, the model in this paper includes a binary variable to represent the period of 2008-2009 in an attempt to quantify the immediate negative effects the global financial crisis had on REIT returns. Ultimately, this model suggests dividend yield, interest coverage, value, and investment growth may have significant impact on risk-adjust return.